STEAM EDUCATIONAL TECHNOLOGY IN PRESCHOOL EDUCATION - Gaffarova Hurriyat Yangiboyevna (Academia Science Repository, 2023)
This article covers the issues of organizing development centers in preschool educational organizations based on a modern approach. Key words: modern approach, center, development, STEAM critical thinking, independent thinking, active communication, individual order.